Neuroblastoma in a patient with Sotos' syndrome. Issue 2 (February 1990) - Nance, M A; Neglia, J P; Talwar, D; Berry, S A
Abstract : Sotos' syndrome, or cerebral gigantism, is a disorder of growth regulation. Tumours have occasionally been reported in children with Sotos' syndrome, but it is uncertain whether this is a coincidence, or whether it is aetiologically related to the underlying disorder of growth. We report a 15 month old child with a paraspinal neuroblastoma and Sotos' syndrome and suggest that children with this condition may be at higher risk for developing tumours than the general population.